Semi-mechanized shoot topping as an alternative for workforce optimization and reduction of operational costs of summer pruning management of grapevines - Würz, Douglas André; Brighenti, Alberto Fontanella; Allebrandt, Ricardo; de Bem, Betina Pereira; Bonin, Bruno Farias; Marcon Filho, José Luiz; Brighenti, Emilio; Rufato, Leo (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to verify the influence of mechanized shoot topping in workforce optimization and reduction of operational costs to perform the grapevine pruning in the highlands of Santa Catarina, Brazil. The experiment was conducted at São Joaquim Experimental Station during the 2016 crop. Shoot topping was performed during phase 75 of the BBCH scale. The treatments consisted of three different shoot topping methods: manual shoot topping, manual shoot topping using a platform coupled to a tractor and semi-mechanized shoot topping performed with a mechanical pruner using a platform coupled to a tractor. The experimental design was completely randomized. Data were submitted to analysis of variance (ANOVA), and Tukey’s test was performed (p ≤ 0.05). The semi-mechanized pruning method presented a 1,106% reduction in time to perform shoot topping in comparison to the manual method. The cost for semi-mechanized topping was R$ 289.70 ha-1, manual topping costed R$ 665.00 ha-1, and manual topping with the platform costed R$ 766.40 ha-1. The semi-mechanization of shoot topping with a mechanical pruner using a platform coupled to a tractor reduces the production costs, in addition to optimizing the use of workforce.